Information and Communication Technology for the Rural Development in Nepal - Kharel, Suman (Tribhuvan University Journal, 2018)
The present article describes the significance of Information and Communication Technology (ICT) for the rural development. It is based on the perception survey about ICT, suggesting that ICT can be very beneficial and powerful tool for facilitating rural development, particularly in the sectors of e-commerce, e-health, e-government services and the most important e-education, training, information and expertise exchange, experience sharing, communication and society engagement. Overall, ICT is an effective tool for the different dimension of rural development.